INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUSKESMAS DI KOTA MATARAM - LALU MUH. KABUL (GANEC SWARA, 2022)
Community Satisfaction Index (CSI) of Community Health Center is an indicator for community to assess services quality and services performance of Community Health Center. The study which is refered to “Permenpan dan RB Nomor 14 Tahun 2017” carried out in 2021 at all Community Health Center in Mataram City. The aim of study is to analysis CSI value, quality services and services performance and correlation between CSI and accreditation status of Community Health Services. The study method used is descriptive with quantitative approach. The result of the study indicated that average value CSI of Community Health Services in Mataram City amount of 77.23 with “B” quality services and “Good” services performance. There is no correlation between CSI and accreditation status of Community Health Services.